Analisis Tipe Hambatan Belajar dan Kesalahan Jawaban Matematika Siswa SMP Pada Konsep Bangun Segiempat dan Alternatif Penyelesaiannya - Mustika, Aulia Musla; Budiyono, Budiyono; Riyadi, Riyadi (Jurnal Pendidikan Progresif, 2018)
Analysis of Student’s Learning Obstacle Type and Wrongness Mathematical Answer of Rectangle Concept and its Altenative Solution. The aim of this study is to analyze the student’s learning obstacle and wrongness mathematical answer on the concept of rectangle. The study involved 28 junior high school students in Surakarta, Central Java, using a quantitative method. Based on the results of data analysis, identified 5 types of student’s learning obstacles based on their answers, that were variation information, concept image, relation between rectangle’s area and circumference, student’s ability to answerthe task, and relation between one concept to anothers . One alternative to overcome the learning obstacle and wrongness mathematical answer was by applying the didactic design which were consisted of RPP, Student Worksheet as well as Prediction of Response and Anticipation Didactic. Key Words: Learning obstacle, wrongness mathematical answer, didactic design DOI: http://dx.doi.org/10.23960/jpp.v8.i1.201801